Edible Nanocoating: The effect of different concentrations of metal nanoparticles incorporated with polysaccharide-based material on antimicrobial and antifungal activity / Ainnur Syamira Kamarudin, Noor Asnida Asli and Nadya Hajar - Kamarudin, Ainnur Syamira; Asli, Noor Asnida; Hajar, Nadya (2021)
Fruit spoilage is very common during the postharvest phase due to extrinsic factors and therefore it renders them unsuitable for human consumption. The microbial and fungal spoilage in fruits results in substantial financial losses throughout the entire supply chain. Applying nanotechnology on the fruit can reduce significant privation. This review elaborates on the antimicrobial and antifungal activity by applications of polysaccharide and metal nanoparticles on fruits. Metal nanoparticles of silver, zinc oxide and titanium dioxide demonstrate attractive antimicrobial and antifungal properties on different concentration nanoparticles such that 0.02% - 8% by weight of polysaccharide could potentially be used. Incorporating nanoparticles in various polysaccharides pullulan, hydroxypropyl methylcellulose (HMPC), carrageenan, chitosan, and pectin polymer matrix increase the efficiency against Aspergillus niger, Bacillus subtilis, Colletotrichum gloeosporioides, Escherichia coli, Fusarium oxysporum, Staphylococcus aureus, and Saccharomyces cerevisiae. All samples display consequential inhibitory effects with increasing metal nanoparticles concentration incorporated with polysaccharide materials. The results obtained possessed a better understanding of different concentrations of polysaccharides incorporated into Ag/ZnO/TiO2 nanoparticles to inhibit fungal and microbial growth which could be used in fighting against postharvest disease and improve the shelf life of fruits. The aims of this research work were to determine and analyse the effects of different concentrations of metal nanoparticles incorporated with polysaccharides-based material on antimicrobial and antifungal activities.